Response of Mustard (Brassica) Varieties to Boron Application (Bangladesh Journal of Agricultural Research, 2012)
An experiment was conducted at the Regional Agricultural Research Station (RARS), Jessore (AEZ11, High Ganges River Floodplain) during 2003-2006 to evaluate the response of different varieties of mustard to boron application. Boron application was made at 0 and 1 kg/ha. The mustard varieties responded to B application. The response of the three Brassica species followed the order: B. napus > B. campestris > B. juncea. The varieties chosen from B. campestris were BARI Sarisha 6, BARI Sarisha 9, and BARI Sarisha 12. The B. napus varieties were BARI Sarisha 7, BARI Sarisha 8, and BARI Sarisha 13. Varieties BARI Sarisha 10 and BARI Sarisha 11 were from the B. juncea group. The seed yield was positively and significantly correlated with the yield contributing characters viz. pods/plant, seeds/pod, and 1000-seed weight, but not with plant height and pod length. This result showed that boron had positive influence on reproductive development, not on vegetative. The result suggests that BARI Sarisha 10 and BARI Sarisha 11 were the most B in-responsive (B efficient) varieties. So the farmers can grow these varieties in the moderately B deficient soils with a minimum dose (0.5 kg/ha) of B application. DOI: http://dx.doi.org/10.3329/bjar.v37i1.11187 Bangladesh J. Agril. Res. 37(1): 137-148, March 2012